Tackling the odds in Development of Sociology Discipline: A Case Study of Institute of Social and Cultural Studies University of the Punjab, Lahore - Iram Rubab; Awan, Waqar Haider (Journal of Peace, Development and Communication, 2021)
Sociology’s demand as a discipline has multiplied because of the unexplored social structures in Pakistan. The present article attempts to explore the challenges faced by the Department of Sociology in the Punjab University - a pioneer department - in the six decades since its establishment. It further analyses the ways in which these challenges were resolved. A pure qualitative approach of holistic case study is employed; in-depth faculty interviews and policy reviews were used. The findings reveal that the classification of sociology as a soft science has led to a lack of governmental funding, availability of trained faculty, and a reluctance of students to opt for the discipline because of market trends. Another issue that comes to the front is a serious dearth of indigenous literature. Improvement measures taken by the department include the establishment of faculty development programs, incentives to engage the faculty in scholarly endeavors, development of libraries and computer labs, promotion of a research culture through a policy of compulsory thesis for degree completion. Collaborations with foreign universities have been extremely fruitful e.g. student cultural exchange program with University of Bielefeld, Germany and, University of Leeds UK. Similarly, faculty development program with Arizona State University in the USA. More importantly, the department has been able to resist governmental pressure to merge with other social science departments. The role of the department has been monumental; however, it can be further improved if the department starts its own research journal to enhance its sociological research capacities